2014
DOI: 10.1097/jto.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes Following Gefitinib and Erlotinib Treatment in Non–Small-Cell Lung Cancer Patients Harboring an Epidermal Growth Factor Receptor Mutation in Either Exon 19 or 21

Abstract: In NSCLC patients harboring EGFR mutation, treatment with gefitinib and erlotinib resulted in similar effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 18 publications
5
30
1
Order By: Relevance
“…However, in the present study, 80% of patients were treated with gefitinib. In patients treated with EGFR-TKIs, brain metastasis has been reported as a risk factor for poorer PFS and OS (13,35). Similarly, in the present study, brain metastasis was the only negative prognostic factor identified by multivariate analysis for OS time.…”
Section: Discussionsupporting
confidence: 62%
“…However, in the present study, 80% of patients were treated with gefitinib. In patients treated with EGFR-TKIs, brain metastasis has been reported as a risk factor for poorer PFS and OS (13,35). Similarly, in the present study, brain metastasis was the only negative prognostic factor identified by multivariate analysis for OS time.…”
Section: Discussionsupporting
confidence: 62%
“…The majority of patients (96.4%) were treated with standard doses of either gefitinib or erlotinib. Although the TKI used differed according to each country's practices, similar outcomes have been reported in earlier studies that compared gefitinib to erlotinib [39, 40]. …”
Section: Resultsmentioning
confidence: 69%
“…Thus, further elucidation of the molecular mechanism underlying LC is essential for the development of new effective therapeutic agents. 3–5 3–5 3–5 As shown in many cancer types, Wnt signaling has emerged as an important pathway in lung carcinogenesis. 5 It was indicated that Wnt signaling is important in non-small-cell LC (NSCLC) cell lines, and decrease in proliferation was determined by inhibition of Wnt.…”
mentioning
confidence: 99%